2019
DOI: 10.22190/fumi1904659a
|View full text |Cite
|
Sign up to set email alerts
|

On the Roots of Total Domination Polynomial of Graphs, Ii

Abstract: Let $G = (V, E)$ be a simple graph of order $n$. A  total dominating set of $G$ is a subset $D$ of $V$, such that every vertex of $V$ is adjacent to at least one vertex in  $D$. The total domination number of $G$ is  minimum cardinality of  total dominating set in $G$ and is denoted by $\gamma_t(G)$. The total domination polynomial of $G$ is the polynomial $D_t(G,x)=\sum_{i=\gamma_t(G)}^n d_t(G,i)$, where $d_t(G,i)$ is the number of total dominating sets of $G$ of size $i$. In this paper, we study roots of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Proof. Let G be a 3-connected graph and D t (G, x) = x γt (x + 2) β , where γ t + β = n. So by Theorem 4.1, we have d t (G, n − 1) = n = 2β, and so 2 , and so G = K 4 , GP . On the other hand, for every k = 2, .…”
Section: Total Domination Polynomial Of Regular Graphsmentioning
confidence: 98%
See 2 more Smart Citations
“…Proof. Let G be a 3-connected graph and D t (G, x) = x γt (x + 2) β , where γ t + β = n. So by Theorem 4.1, we have d t (G, n − 1) = n = 2β, and so 2 , and so G = K 4 , GP . On the other hand, for every k = 2, .…”
Section: Total Domination Polynomial Of Regular Graphsmentioning
confidence: 98%
“…Also the first authors has studied graphs with few domination roots in [1]. In [2] we have shown that all roots of D t (G, x) lie in the circle with center (−1, 0) and the radius δ √ 2 n − 1, where δ is the minimum degree of G. Also we proved that for a graph G of order n, if δ ≥ 2n 3 , then every integer root of D t (G, x) lies in the set {−3, −2, −1, 0}. Motivated by these integer roots, and a conjecture in [2] which states that for every integer root r of D t (G, x), r ∈ {−3, −2, −1, 0}, we study graphs with exactly two total domination roots {−1, 0}, {−2, 0} and {−3, 0}, in this section.…”
Section: Graphs With Exactly Two Total Domination Roots {−1 0}mentioning
confidence: 99%
See 1 more Smart Citation
“…For many graph polynomials, their roots have attracted considerable attention, both for their own sake, as well for what the nature and location of the roots imply. The roots of the chromatic polynomial, independence polynomial, domination polynomial and total domination polynomials have been studied extensively [1,2,5,8,10,11,12,14,26]. We investigate here independence domination roots, that is, the roots of independent domination polynomials.…”
Section: Introductionmentioning
confidence: 99%
“…The study of coalition graphs, particularly for paths, cycles, and trees, was conducted in [9]. The concept of total coalition was introduced and explored in [1], while the coalition parameter for cubic graphs of order at most 10 was investigated in [2].…”
mentioning
confidence: 99%